Cualidades culturales y turísticas que presenta Granja Porcón para el desarrollo sostenible del turismo rural comunitario. - Marquina Cueva, Miguel Angel (2019)
The thesis entitled Tourism and Cultural Qualities presented by Granja Porcón for the sustainable development of Community Rural Tourism was developed in the town of Granja Porcón, district of Cajamarca, province of Cajamarca, Cajamarca region. _x000D_ The thesis proposes the identification of tourist and cultural qualities that present Granja Porcón, an important and consolidated destination within the tourist offer of the Cajamarca region. It is both qualities and their identification that allowed a diagnosis to be made in order to obtain important information. On the cultural side, it has been identified that Granja Porcón has archaeological evidence, such as the site known as Cerro Grande, different sections of the Inca Trail and some structures of what used to be the old Casa Hacienda Porcón, in the same way it was recognized that community remain intangible cultural events such as the textiles, activity in which natural elements and minerals for pigmentation of wool are used, as well as techniques that refuse to be lost as the loom waist, and incorporating new techniques and instruments such as the pedal loom. On the side of the local cuisine, it was identified that the menu includes dishes that are part of the identity of Cajamarca, in addition to the use of typical products from the area and the invention of new dishes made with mushrooms. The sustainable use of vicuña fiber through the chaccu and the shearing, the call of the cows by their name and the agricultural tasks, are evidences of the cultural richness with which the community of Granja Porcón counts. _x000D_ On the tourist side it was possible to appreciate that it has the basic services that a tourist would need when arriving to this place. Five lodging establishments, three restaurants, the local guide and a transportation company that covers the Cajamarca - Granja Porcón route and vice versa. _x000D_ Both elements, tourist and cultural, are also part of the offer in rural community tourism offered by Granja Porcón, a project that forms part of the Rural Community Tourism memorial prepared by MINCETUR.